Phytochemical Study and in vitro Cytotoxic Effect of Ajuga chamaecistus ssp. tomentella - Sadati, N.; Ostad, S.N.; Karimian, Z.; Shams Ardekani, M.R.; Akbarzadeh, T.; Hadjiakhoondi, A.; Khanavi, M. (Asian Journal of Chemistry, 2012)
In this study total methanolic extract (80 %), n-hexane, diethyl ether, hydroalcoholic fractions and three major compounds from aerial parts of Ajuga chamaecistus ssp. tomentella were investigated for in vitro cytotoxic effect against cancer (HT-29, Caco-2, T47D) and normal (NIH 3T3) cell lines by the MTT assay. The n-hexane fraction showed cytotoxicity against all cell lines with IC50 ³ 200 μg/mL and the diethyl ether fraction exhibited medium cytotoxic effect against HT-29 cell line (IC50 311.01 ± 9.0 μg/mL). The diethyl ether fraction was chromatographed on silica gel using a chloroform-ethyl acetate-methanol gradient system to give compound 1, 2 and 3. The structure of compound 1, 2 and 3 were determined to be 20-hydroxyecdysone, cyasterone and 8-acetylharpagide, respectively, by means of spectroscopic analysis. These three major compounds were inactive in cytotoxicity evaluation (IC50 > 400 and 800 μg/mL), suggesting little correlation between the degree of cytotoxic effect of the diethyl ether fraction and the isolated compounds.